2018
DOI: 10.1128/genomea.01554-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Acinetobacter and Bacillus Strains Isolated from Spacecraft-Associated Surfaces

Abstract: We report here the draft genome sequences of four strains isolated from spacecraft-associated surfaces exhibiting increased resistance to stressors such as UV radiation and exposure to H2O2. The draft genomes of strains 1P01SCT, FO-92T, 50v1, and 2P01AA had sizes of 5,500,894 bp, 4,699,376 bp, 3,174,402 bp, and 4,328,804 bp, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Analyses of the ISS microbiome have already been performed, including microbial analyses of ISS debris and dust 1316 , the study of the astronauts’ microbiome 17 , the characterization of bacterial and fungal isolates from the ISS 18,19 , and the (molecular) microbial analysis of swab and wipe samples taken inside the ISS 20 . A study investigating the growth behavior of nonpathogenic (terrestrial) bacteria aboard the ISS found no changes in most bacteria, given that they have enough nutrients 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the ISS microbiome have already been performed, including microbial analyses of ISS debris and dust 1316 , the study of the astronauts’ microbiome 17 , the characterization of bacterial and fungal isolates from the ISS 18,19 , and the (molecular) microbial analysis of swab and wipe samples taken inside the ISS 20 . A study investigating the growth behavior of nonpathogenic (terrestrial) bacteria aboard the ISS found no changes in most bacteria, given that they have enough nutrients 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications focused on the microbial analysis of ISS debris and dust (12–15), the study of the astronauts’ microbiome (16), the characterization of bacterial and fungal isolates from the ISS (17,18) and the (molecular) microbial analysis of swab and wipe samples taken inside the ISS (19). A study investigating the growth behavior of non-pathogenic (terrestrial) bacteria aboard the ISS found no changes in most bacteria, given that they have enough nutrients (11).…”
Section: Introductionmentioning
confidence: 99%
“…Building upon established research[29, 38], our analysis of proteomic alterations points to a significant enrichment across various protein classes. A particularly noteworthy observation is the global glycine enrichment, a phenomenon that aligns with findings from earlier studies on Acinetobacter sp., a desiccation-tolerant organism[16, 30, 40]. Historically, these organisms have not only displayed enhanced hydrophilicity but have also shown a fortified resistance to ionizing radiation, a stress factor intrinsically tied to redox reactions.…”
Section: Discussionmentioning
confidence: 99%